Epigenomics in health and disease - Fraga, Mario; Fernandez, Agustin F. (London : Academic Press, 2015)
Reviews the technologically-driven study of the oganismal epigenome and associated translational impacts on future prognosis, diagnosis and therapies of disease. With next-generation sequencing technologies shaping our current knowledge of the role of epigenetics in normal development, aging, and disease, Epigenomics in Health and Disease discusses the consequences for diagnostics, prognostics, and disease-based therapies made possible by the study of the complete set of epigenetic modifications to the genetic material of human cells. Chapters also explore the latest findings of epigenome-wade research in disease-based profiling, epidemiological implications, epigenome-wide epigenetic studies, the cancer epigenome, and other pervasive disease categories. With coverage pertinent both to basic biology and translational research, Epigenomics in Health and Disease will be of particular interest for medical and bioscience researches and students seeking current translational knowledge in epigenesis and epigenomics. Key Features Critical reviews provide the means for reviewing and analyzing the epigenome as a whole as well as its translational potential Combines basic epigenomic knowledge with methodological and biostatistical topics related to technology and date analysis Includes coverage of relatively new topics including DNA methylation dynamics during development and differentiation, genome-wide histone post-translational modifications during development and differentiation, and genome-wide DNA methylation changes during aging.
The role of the genetic code in the DNA methylation landscape formation / Holger Heyn -- DNA methylation microarrays / Marina Bibikova -- Ultra-deep sequencing of bisulfite-modified DNA / Tingting Qin, Yongseok Park, Maria E. Figueroa and Maureen A. Sartor -- Bioinformatics tools in epigenomics studies / t Genome-wide DNA methylation changes during aging / Kevin C. Johnson and Brock C. Christensen -- The dynamics of histone modifications during aging / Anthony J Bainor and Gregory David -- Epigenomic studies in epidemiology / Valentina Bollati, Valeria Motta, Simona Iodice and Michele Carugno -- The DNA methylomes of cancer / t Genome-wide DNA and histone modification studies in metabolic disease / t
Includes index.
Print version record.
Includes bibliographical references at the end of each chapters and index.
Keywords: Epigenetics; Medical genetics; SCIENCE -- Life Sciences -- Evolution; Epigenetics; Medical genetics; Epigenomics -- methods; Epigenesis, Genetic; Gene Expression Regulation; Electronic books; Electronic books